“Three zones” method for coal mine water hazard control and its significance - Yifan ZENG; Chao YU; Qiang WU; Linger ZHAO; Shangxian YIN; Bocheng ZHANG; Zeyang LIU; Yashuai CUI; Xuedong KAN; Hao HUANG (Meitan xuebao, 2024)
In order to systematically understand the various types of water hazards and standardize the management of water prevention and control work in coal mines, the National Mine Safety Administration in June 2022 extended the “three zones” management methodology for old goaf water prevention and control to more types of water hazards, such as roof water, floor water, and structural water. However, in the process of dividing the “three zones” of water prevention and control in coal mines, it is revealed that the water damage causing factors and water damage management situation are not closely linked with the division standard, and that technically different divisions are not made for different coal seams and mining areas, and there are inconsistencies in the scope of the division area, and the standardization and timeliness of the division results. Accordingly, combined with the purpose of water hazard prevention and control “three zones” division, compared the similarities and differences between the new and old “three zones” division work, this paper clarifies the degree of hydrogeological conditions survey, water hazard analysis, water hazard management as elements of the division principles, and determines the technical path of the division of the “three zones”. Combining the characteristics of five common types of water hazards in coal mines, the paper puts forward the division method of different types of water hazards, that is: surface water hazard should be divided according to the distribution and development characteristics of surface water bodies in the mining area and the degree of influence of atmospheric precipitation, landslides and other geological disasters in mining. The roof water hazard should be divided according to whether there is a strong water-rich aquifer, a medium water-rich but hydrostatic reservoir-rich aquifer, a loose aquifer. The floor water hazard should be divided according to the relationship between the thickness of the floor water barrier and the depth of the floor mine pressure damage zone in the coal seam pressure mining area, as well as the size of the floor water inrush coefficient. The old goaf water hazard should be divided according to the distribution range and amount of water in the mine and the surrounding mines. The structural water hazards should be divided according to the water-richness, water content, and water source conduction of geological structures and bad geological bodies such as faults, trap columns and caves in the mining area. The key points and difficulties of the division work include the clear division of time and space scope, the comprehensive analysis of division standards, the clear management responsibilities for the “three zones”, and the dynamic transformation of division results. On this basis, typical coal mines with various types of water hazards and complex hydrogeological conditions are selected as case studies. Following the principle of division, according to the division standard, the mineable zone, the slow mining zone and no-mining zone are divided by the method of separating coal seams and mining areas, and detailed explanations are given. The significance of carrying out the division of the “three zones” for water hazard prevention and control is clarified, which can enhance the comprehensive detection level, strengthen the prediction ability, and identify the direction of water hazard management in order to guide and standardize the division of the “three zones” for water prevention and control in the coal mines of China.